New approaches to selective laser trabeculoplasty - S. Yu. Petrov; R. P. Poleva (Biomedical Photonics)
Selective laser trabeculoplasty (SLT) is the “golden standard” of laser glaucoma surgery. Its efficacy can be compared to pharmacological therapy, while in some cases its advantages may even lead to a more stable hypotensive effect. SLT may be used as a primary treatment for primary open-angle glaucoma patients and patients with ocular hypertension, while also considered safe and effective in cases when a repeat procedure is required. SLT may potentially decrease the demand for antiglaucoma drugs, improve patient’s response to treatment, make the treatment more comfortable and overall increase the patient’s quality of life. New modifications of standard laser treatment procedures have been emerging lately. This article summarizes scientific data on the efficacy and safety of the new generation of laser trabeculoplasty. It specifies the charateristics of micropulse laser trabeculoplasty (MLT), pattern-scanning trabeculoplasty (PLT) and titaniumsapphire laser trabeculoplasty (TSLT) and recounts the latest research dedicated to them.